Photodynamics of oxybenzone sunscreen: Nonadiabatic dynamics simulations - Li, Chun-Xiang; Guo, Wei-Wei; Xie, Bin-Bin; Cui, Ganglong (The Journal of chemical physics, 2016)
Herein we have used combined static electronic structure calculations and “on-the-fly” global-switching trajectory surface-hopping dynamics simulations to explore the photochemical mechanism of oxybenzone sunscreen. We have first employed the multi-configurational CASSCF method to optimize minima, conical intersections, and minimum-energy reaction paths related to excited-state intramolecular proton transfer (ESIPT) and excited-state decays in the 1 ππ ∗, 1 nπ ∗, and S0 states (energies are refined at the higher MS-CASPT2 level). According to the mapped potential energy profiles, we have identified two ultrafast excited-state deactivation pathways for the initially populated 1 ππ ∗ system. The first is the diabatic ESIPT process along the 1 ππ ∗ potential energy profile. The generated 1 ππ ∗ keto species then decays to the S0 state via the keto 1 ππ ∗/gs conical intersection. The second is internal conversion to the dark 1 nπ ∗ state near the 1 ππ ∗ /1 nπ ∗ crossing point in the course of the diabatic 1 ππ ∗ ESIPT process. Our following dynamics simulations have shown that the ESIPT and 1 ππ ∗ → S0 internal conversion times are 104 and 286 fs, respectively. Finally, our present work demonstrates that in addition to the ESIPT process and the 1 ππ ∗ → S0 internal conversion in the keto region, the 1 ππ ∗ → 1 nπ ∗ internal conversion in the enol region plays as well an important role for the excited-state relaxation dynamics of oxybenzone.